Special Schools as NPDL Resource Centers for Inclusion: Reposisi SLB dan ULD sebagai Pusat Sumber NPDL Inklusif - Nugraheni, Khoiri; Tarsidi, Iding (Universitas Muhammadiyah Sidoarjo, 2026)
General Background: Inclusive education prioritizes equity, participation, and quality learning for all students within unified school systems. Specific Background: In Indonesia, Special Schools (SLB) and Disability Service Units (ULD) are mandated to support inclusive education and increasingly operate as pedagogical resource centers aligned with the New Pedagogies for Deep Learning (NPDL) framework. Knowledge Gap: Empirical and conceptual studies rarely explain how these institutions systematically integrate collaborative inquiry with NPDL to support inclusive transformation at the system level. Aims: This study formulates a conceptual framework that repositions SLBs and ULDs as NPDL-oriented resource hubs through structured collaborative inquiry cycles. Results: Based on a structured literature review (2020–2024) and thematic synthesis, findings indicate that SLBs and ULDs provide assessment, mentoring, co-teaching, and professional learning communities corresponding to the NPDL Inquiry Cycle—Assess, Design, Implement, Measure, Reflect, and Change—while leadership and institutional capacity serve as key enabling conditions. Novelty: The study integrates inclusive education principles, NPDL architecture, and collaborative inquiry into a coherent reform model centered on resource-based institutional transformation. Implications: The framework informs policy and practice by outlining leadership preparation, systemic support, and structured professional collaboration as foundations for sustainable, competency-based inclusive education. Highlights• Thematic synthesis (2020–2024) confirms institutional mentoring, assessment, and co-teaching functions within inclusive networks.• Inquiry cycles align deep learning competencies with structured professional collaboration across school systems.• Leadership preparation and systemic support are foundational for sustainable educational reform. KeywordsInclusive Education; Special Schools; Disability Service Units; Collaborative Inquiry; New Pedagogies For Deep Learning